Comparative Analysis Of Income Of Farming Income In Superior Variety With Local Varieties In Kuantan Hilir District, Kuantan Singingi Regency - Enin Ernia; Elfi Indrawanis; Meli Sasmi (Baselang, 2021)
This study aims to 1) Determine the difference in income of superior varieties of paddy rice farmers with local varieties in the District of Kuantan Hilir. 2) Knowing the level of efficiency of superior variety and local varieties of paddy farming in Kuantan Hilir Subdistrict. Sampling was done purposively. Respondents taken 30 people from superior varieties of paddy rice farmers amounted to 15 farmers and 15 varieties of local rice farmers. Data analysts use mathematical analysis and statistical analysis. Mathematical analysis uses profit analysis and business efficiency analysis (R / C). While the statistical analysis is by using the Independent Sample T Test and One-Way Anova test to see the similarity of variants. The results showed that mathematically the average income of superior varieties of local rice farmers and different local varieties, the average income of superior varieties of rice was Rp 2.708.407,00while local varieties of rice were Rp.965.933,00With the ratio of efficiency (R / C) superior varieties of rice 1.83 while local varieties of rice 1.69.